New soluble polyamides with high transparence and improved gas separation properties. Issue 1 (16th September 2020) - Jiang, Cairong; Wang, Chenyi; Yu, Bin; Zhao, Xiaoyan; Li, Jian; Ren, Qiang
Abstract: Based on the aromatic diamine monomer containing di-tert-butylbenzene and methyl groups, this work proposes its polymerization with four different dicarboxylic acids. The prepared polyamides (PA 3a–3d ) were characterized by GPC, FTIR, 1 H NMR, mechanical, thermal, optical and gas separated techniques. They exhibited high solubility and good optical transparency. Their optical transmittance at 450 nm wavelength was in the range of 81.4%–86.8%, and the cutoff wavelength was in the range of 327–352 nm. The membranes also had good mechanical properties with tensile strength of 79.7–91.4 MPa, elongations at breaks of 9.0–10.9% and initial modulus of 1.5–1.9 GPa. Meanwhile, these membranes possessed good thermal properties with glass transition temperature ( T g ) values of 226–246 °C. The permeability of CH4, N2, and CO2 for these membranes was tested by constant pressure-variable volume method. The PA 3d containing tert-butyl moiety in the diacid units exhibited highest permeability (PCO2 = 31.4 and PN2 = 1.9) whereas PA 3c containing hexafluoroisopropylidene moiety exhibited highest selectivity (CO2 /CH4 = 22.2). Graphical Abstract: